👤

Answer :

Answer:

see explanation

Step-by-step explanation:

(a)

Substitute the x- coordinate into the right side of the equation and if y is equal to the y- coordinate of the ordered pair then it is a solution

y = 2(- 3) + 2 = - 6 + 2 = - 4 ≠ 2

Then (- 3, 2 ) is not a solution to the equation

(b)

Substitute the coordinates of the ordered pair into the left side and if the value obtained is equal to the right side then it is a solution.

2(1) + (- 3) = 2 - 3 = - 1 ← True

Then (1, - 3 ) is a solution to the equation